A twenty-first-century torch of freedom for Muslim women: Sarah Maple's Fighting Fire with Fire No. 2. Issue 3 (1st December 2020) - Heins, Julia
This article closely examines a work of art in light of the politics, popular culture and social dynamics surrounding its maker. Through a close examination of the formal elements and signs included in Sarah Maple's 2007 self-portrait photograph, Fighting Fire with Fire No. 2, feminist values are explored using a semiotic analysis. In the end, the article champions Sarah Maple's work as a powerful commentary that combats Muslim stereotypes and liberates women from social and religious taboos.